El desarrollo integral fortalecido por la música en niños y niñas del primer año de educación básica paralelo “A” en la escuela Mariscal Antonio José de Sucre de la parroquia La Matriz, cantón Saquisilí, provincia de Cotopaxi; en el año lectivo 2014-2015 - Iza Guanoquiza, Ana Cristina (2015)
This work contains aspects that will help children to have better learning in cognitive, motor and affective aspects, through music strengthen the comprehensive development of children, this research is based on practical and theoretical because that information has been extracted from different authors specializing in this topic, it I contributes greatly to raising activities that guide the teaching of the First level EGB Parallel "A" to creative dynamic classes where teaching - learning doesn´t be monotonous or repetitive and children are spontaneous with themselves into the process, the importance of this work is justified that the methodology is not according in order to obtain an optimal integral development in children, not being is not used treated early future will not develop attitudes and skills that strengthen their autonomy and better development, this proposal through a tutorial based on the music in order to improve the children´s skills on the other hand to provide timely and relevant education, the development of musical workshops will very helpful for the educational community, they will find different fun activities that will help them build background knowledge according to their age in a better teaching-learning process.